2009
DOI: 10.1111/j.1600-0560.2009.01356.x
|View full text |Cite
|
Sign up to set email alerts
|

Panniculitis–an unusual cutaneous manifestation of systemic sclerosis

Abstract: Systemic sclerosis (SSc) is an autoimmune systemic disease characterized by small vessel involvement that leads to tissue ischemia and fibroblast stimulation resulting in accumulation of collagen (fibrosis) in the skin and internal organs. Lipomembranous panniculitis is a peculiar type of fat necrosis and has been reported with clinical conditions, commonly with peripheral vascular diseases. We describe a case of a 43-year-old woman with SSc manifestations, who presented with black scaly skin plaques, associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
(21 reference statements)
1
10
0
Order By: Relevance
“…Furthermore, lipomembranous changes were observed in the biopsy specimens taken from the forearm. In another case, a biopsy from the abdominal hard hyperchromic plaque with coalescent and painful nodules revealed lipomembranous panniculitis [6]. In the present case, lipomembranous changes were observed in the specimens from both forearm and finger unrelated with the lesion of NCFN.…”
Section: Sirsupporting
confidence: 54%
See 1 more Smart Citation
“…Furthermore, lipomembranous changes were observed in the biopsy specimens taken from the forearm. In another case, a biopsy from the abdominal hard hyperchromic plaque with coalescent and painful nodules revealed lipomembranous panniculitis [6]. In the present case, lipomembranous changes were observed in the specimens from both forearm and finger unrelated with the lesion of NCFN.…”
Section: Sirsupporting
confidence: 54%
“…Snow et al reported three cases of morphea in their series, which presented with lipomembranous changes on the morpheaform plaques of the back, legs, and calf [4]. To date, only a few cases of SSc similar to ours were reported [5,6]. In one case, mobile nodules appeared on the forearm, and histological examination revealed NCFN [5].…”
Section: Sirmentioning
confidence: 65%
“…Most lesions present with indurated, subcutaneous lesions in the lower extremities 7. Panniculitides are less commonly seen in the arms, thighs, calves and gluteus 8 9. One case report described a woman presenting with panniculitis of the arm who was subsequently diagnosed with diffuse SSc 9.…”
Section: Discussionmentioning
confidence: 99%
“…Panniculitis[13] and cutaneous hyperpigmented reticulate scleroderma[14] are some recently described unusual cutaneous manifestation of SSc. We did not find any such cases in the present series.…”
Section: Discussionmentioning
confidence: 99%